AI in the Essay Classroom: Perceptions, Practices, and Plagiarism among Pre-Service English Teachers - Syamsiarna Nappu; Muhayyang, Maemuna; Hasnawati, Hasnawati; Rifqah, Rifqah (Corolla International Conference, 2025)
This study explores the integration of Chat-based Artificial Intelligence (AI) tools, particularly ChatGPT, into the academic writing practices of English Language Education students at Universitas Negeri Makassar. Employing a qualitative single case study design, this research investigates how students leverage AI tools for vocabulary enrichment, grammar correction, maintaining originality, and avoiding plagiarism during essay writing. Data were collected through semi-structured interviews with 11 students enrolled in the Essay Writing course. Thematic analysis revealed that students generally perceived Chat-based AI as a supportive mechanism for improving vocabulary and sentence structure. Most participants reported enhanced learning through iterative engagement with AI-generated suggestions. However, concerns about originality and unintentional plagiarism were prevalent, prompting strategies such as paraphrasing and content modification. While AI tools facilitated more structured and coherent essays, students emphasized the importance of integrating their own ideas to maintain authenticity. The findings underscore the dual role of AI in both empowering and challenging students’ writing autonomy. The study concludes by advocating for ethical AI use guidelines and pedagogical frameworks that emphasize critical engagement over content dependence.